Introduction to statistical physics - Salinas, Silvio R. A. (Springer New Delhi, 2001)
This textbook covers the basic principles of statistical physics and thermodynamics. The text is pitched at the level equivalent to first-year graduate studies or advanced undergraduate studies. It presents the subject in a straightforward and lively manner. After reviewing the basic probability theory of classical thermodynamics, the author addresses the standard topics of statistical physics. The text demonstrates their relevance in other scientific fields using clear and explicit examples. Later chapters introduce phase transitions, critical phenomena, and non-equilibrium phenomena.
With 67 illustrations
Keywords: Statistical physics